Factors Influencing Pre-Exposure Prophylaxis Among Youths Aged 15 -24 Years in Suba Sub-County, Homabay County - Odie, Emeldah Adhiambo (JOOUST, 2021)
Pre-exposure prophylaxis is the use of an antiretroviral medication to prevent the acquisition of HIV by uninfected persons. Pre-exposure prophylaxis may either be taken orally, using an antiretroviral drug available for treatment of HIV infection (tenofovir plus emtricitabine) or topically as a vaginal gel containing tenofovir. In the wake of rising HIV infections in youths, PrEP provides an opportunity to reduce the HIV epidemic. This study was specifically set out to determine the socio-demographic factors, knowledge assessment and identify service delivery factors influencing uptake of PrEP among 394 youths aged between 15-24 years in Suba sub-County. The study was guided by conceptual frame work model. It was conducted in Suba sub-County in twenty-four health facilities offering PrEP and HIV services. The study employed descriptive cross-sectional design using both quantitative and qualitative data collection methods. Study population was estimated to be 25514 youths aged 15-24 years from whom a sample size of 394 was drawn. A structured questionnaire, and in-depth interview guide were used to collect data. Quantitative data was analyzed using SPSS version 23. Inferential statistics Chi-square test, multivariate regression analysis and ANOVA, were conducted to examine the relationship between socio-demographic and PrEP knowledge assessment of the respondents. Qualitative data was analyzed through content analysis by examining emerging themes. The Majority of the respondents were 245(62%) females,278(71%) aged 19 and above years, 227(57%) singles,283(72%) unemployed,386(98%) Christians and 226(57%) had attained secondary education and above. The study revealed that occupation and means of transport had statistical significance relationship with (p-value -0.014) on the Chi-square test done. Theme poor road network was realized on the in-depth interview conducted with HCP that hinders clients to access health facilities for PrEP services. There was the weak linear relationship between knowledge on PrEP and PrEP uptake among youths on multivariate regression analysis done at (R Square = 0.193701), this shows that PrEP knowledge had effects on PrEP uptake. The themes inadequate staff training on PrEP, client stigma, lack of parental consent to age below 18years, negative staff attitude to offer PrEP services and inadequate laboratory facilities was realized. The facility administration should integrate services within the facility which are youth friendly in order to improve PrEP uptake. The office of the CASCO should upscale PrEP services in all the sectors.